AGED PEOPLE’S PERCEPTION ABOUT THE TRANSITIONAL CARE PROVIDED BY A MULTIPROFESSIONAL HOME-BASED ASSISTANCE TEAM - Quintans, Jeane Roza; Melleiro, Marta Maria (Cogitare Enfermagem, 2023)
Objective: to understand the aged people’s perception about the care provided by a Multiprofessional Home-based Assistance Team in the city of São Paulo - Brazil. Method: a qualitative study using oral life stories. The data were collected between August 2020 and October 2021 by means of semi-structured interviews. The sample consisted of nine aged women assisted by the Multidisciplinary Home-based Assistance Team. The data were treated according to oral life stories, presented in the form of narratives and categorized. Results: seven thematic categories emerged from the narratives. The participants’ perception of the health care provided by the team was positive and necessary, mainly because it favored access to the resources provided by the Unified Health System. Conclusion: the importance of home-based care for care continuity for aged people is highlighted. The study reinforced the need to include the finitude process in the planning of care actions in health services.